FEATURES OF THE USE OF SYNONYMS IN RUSSIAN SPEECH (Proceedings of International Educators Conference, 2024)
The grammar of the Russian language is characterized by a wealth of synonyms. This article discusses the specific aspects of the use of synonyms in spoken Russian language and analyzes with the help of examples.